Puerto Rico - Davis, Lucile (New York : Children's Press, 2000)
Describes the geography, plants, animals, history, economy, religions, culture, sports, arts, and people of Puerto Rico.
Includes bibliographical references and index.
Keywords: Puerto Rico -- Juvenile literature; Puerto Rico